BUILDING INDEPENDENT VILLAGES THROUGH COLLABORATIVE GOVERNANCE BY VILLAGE-OWNED ENTERPRISES (BEST PRACTICE FROM PANGGUNGHARJO VILLAGE, CENTRAL JAVA, INDONESIA) - Sri Juni Woro Astuti; Falih Suaedi (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Palangka Raya, 2018)
This study aims to develop a collaborative governance model applied by village-owned enterprises called